Re-analysis of Adema et al. (2025a) - Riccardo Ciacci (Institute for Replication (I4R), 2025)
Adema et al. (2025a) critically reassesses the findings of Ciacci (2024), arguing that the reported effects result from statistical errors and flawed empirical implementation. This response systematically addresses those claims by applying their proposed methodology to the corrected sample outlined in Ciacci (2025). The analysis confirms that the large positive estimated coefficient linking the criminalization of sex purchase to reported rape cases is not attributable to technical or coding mistakes. Rather, the differences in robustness observed in Ciacci (2025) arise from the estimation of a distinct target parameter and the implementation of alternative robustness checks, not from errors in the original study. In addition, this reply identifies methodological and procedural issues in Adema et al. (2025a), including comparisons across nonequivalent specifications and limited consideration of contextual assumptions. The response advocates for a more transparent, respectful, and collaborative approach to replication, particularly when addressing sensitive topics that demand scientific integrity and academic rigor.
Keywords: 330